High vs. Low Initial Oxygen to Improve the Breathing Effort of Preterm Infants at Birth: Study Protocol for a Randomized Controlled Trial - Dekker, Janneke; Hooper, Stuart B.; Giera, Martin; McGillick, Erin V.; Hutten, G. Jeroen; Onland, W.; van Kaam, Anton H.; te Pas, Arjan B. (Frontiers in Pediatrics, 2019)
Background Although most preterm infants breathe at birth, their respiratory drive is weak and supplemental oxygen is often needed to overcome hypoxia. This could in turn lead to hyperoxia. To reduce the risk of hyperoxia, currently an initial low oxygen concentration (21-30%) is recommended during stabilisation at birth, accepting the risk of a hypoxic period. However, hypoxia inhibits respiratory drive in preterm infants. Starting with a higher level of oxygen could lead to a shorter duration of hypoxia by stimulating breathing effort of preterm infants, and combined with subsequent titration based on oxygen saturation, prolonged hyperoxia might be prevented. Study design This multi-center randomized controlled trial will include 50 infants with a gestational age between 24-30 weeks. Eligible infants will be randomized to stabilization with an initial FiO2 of either 1.0 or 0.3 at birth. Hereafter, FiO2 will be titrated based on the oxygen saturation target range. In both groups, all other interventions during stabilisation and thereafter will be similar. The primary outcome is respiratory effort in the first 5 minutes after birth expressed as average minute volume/kg. Secondary outcomes include inspired tidal volumes/kg, rate of rise to maximum tidal volume/kg, percentage of recruitment breaths with tidal volumes above 8mL/kg, duration of hypoxia and hyperoxia and plasma levels of markers of oxidative stress (8-iso-prostaglandin F2α). Discussion Current resuscitation guidelines recommend oxygen titration if infants fail to achieve the 25th centile of the SpO2 reference ranges. It has become clear that, using this approach, most preterm infants are at risk for hypoxia in the first five minutes after birth, which could suppress the breathing effort. In addition, for compromised preterm infants who need respiratory support at birth, higher SpO2 reference ranges in the first minutes after birth might be needed to prevent prolonged hypoxia. Enhancing breathing effort by achieving an adequate level of oxygenation could potentially lead to a lower incidence of intubation and mechanical ventilation in the delivery room, contributing to a lower risk on lung injury in high-risk preterm infants. Measuring 8-iso-prostaglandin F2α could lead to a reflection of the true amount of oxygen exposure in both study groups.